2018
DOI: 10.1002/2017jc013553
|View full text |Cite
|
Sign up to set email alerts
|

Wind‐Driven Cross‐Shelf Exchange—West Spitsbergen Current as a Source of Heat and Salt for the Adjacent Shelf in Arctic Winters

Abstract: Cross‐shelf exchange can drive substantial hydrographic changes on shelves and along slopes. In this study, time series from moorings, profiles collected by a tagged seal, atmospheric reanalysis data, and weather regimes classification were used to investigate cross‐shelf exchange at the slope‐shelf interface south‐west of Spitsbergen during the four winters 2011–2014. Assessment of Ekman transport (ET) as a driving force and linking cross‐shelf exchange to large‐scale weather patterns were in focus. Strong po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…CTD transects from the fjord head in Brepollen to the fjord mouth show that the surface and intermediate layers of Hornsund were about 2 °C warmer in late July 2013 than at the same time in 2010; a difference they relate to more water of Atlantic origin being present on the shelf in 2013. Winter time series (December–March) at 103‐m depth of temperature and salinity from the shelf outside Hornsund are presented by Goszczko et al (). Their results show that the shelf was occupied by cold coastal water at freezing point from late December 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTD transects from the fjord head in Brepollen to the fjord mouth show that the surface and intermediate layers of Hornsund were about 2 °C warmer in late July 2013 than at the same time in 2010; a difference they relate to more water of Atlantic origin being present on the shelf in 2013. Winter time series (December–March) at 103‐m depth of temperature and salinity from the shelf outside Hornsund are presented by Goszczko et al (). Their results show that the shelf was occupied by cold coastal water at freezing point from late December 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Large‐scale atmospheric forcing (Christoffersen et al, ; Cottier et al, ; Muckenhuber et al, ; Nilsen et al, ) as well as, or in addition to, generation and propagation of internal Kelvin waves into fjord systems (Inall et al, ; Jackson et al, ; Svendsen et al, ) have been regarded as important mechanisms for driving cross‐shelf and shelf‐fjord exchange both on the west coast of Spitsbergen and in Greenland fjords. Recent studies showed strong correlation between cross shelf Ekman‐Transport and temperature and salinities on the shelf outside Hornsund and in the Hornsund interior during the same periods (Goszczko et al, ). Local forcing inside the fjords from sea ice production and cooling of the water column affects the properties of the local water masses, which in turn can be a controlling factor for inflowing water (Nilsen et al, , ; Tverberg et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…where is the efficiency coefficient, is the turbulent dissipation rate and N is the buoyancy frequency. The efficiency coefficient is variable and uncertain but is commonly set to 0.2, which is the recommended value for typical oceanographic applications (Gregg et al, 2018). The heat flux is calculated from the shear measurements using K ρ with = 0.2 and a vertical scale of 10 m for the background temperature and density gradients.…”
Section: Turbulent Heat Fluxesmentioning
confidence: 99%
“…Patches of warm AW from the WSC are found on the shelf (Nilsen et al, ). The upwelling of AW on the shelf is substantially wind driven (Goszczko et al, ) with Ekman transport oriented toward the shelf in the presence of southerly winds. Warm AW is found on the shelf in winter when cyclones and storms are frequent (Cottier et al, ).…”
Section: Introductionmentioning
confidence: 99%